Análisis de las partidas de las cuentas por pagar y por cobrar de la empresa COERIEGO S.A. - Muñoz Mora, Julian Jose (2020)
This case study is titled Analysis of the accounts payable and receivable items of the year 2017 - 2018 of the company Coeriego S.A. It is oriented to the study of all its payment obligations and what are its main disadvantages when making its sales on credit since it does not recover its portfolio in an estimated time creating the account receivable from clients. The company has been struggling year after year to be able to stay in the market since it has had many problems when making sales on credit and these in turn generate problems when making a new investment since it does not have the necessary resources to obtain new products in its warehouse, since at present they are handled with products only by order.